Future control and automation : Proceedings of the 2nd international conference on future control and automation (ICFCA 2012) - Volume 1 - Deng, Wei (Lecture Notes in Electrical Engineering, 2012)
This volume Future Control and Automation- Volume 1 includes best papers selected from 2012 2nd International Conference on Future Control and Automation (ICFCA 2012) held on July 1-2, 2012, Changsha, China. Future control and automation is the use of control systems and information technologies to reduce the need for human work in the production of goods and services. This volume can be divided into five sessions on the basis of the classification of manuscripts considered, which is listed as follows: Identification and Control, Navigation, Guidance and Sensor, Simulation Technology, Future Telecommunications and Control